Optimalisasi Animasi 3D Dalam Penyampaian Informasi Prosedur Pendaftaran Siswa Baru Di SMK - siti_umul, nurul_hidayah; Udi Firmansyah, Ada (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
The advancement of technology in information and communication has enabled innovative multimedia applications in education. This research examines the use of Plotagon to develop 3D animations that illustrate the student registration process at SMKN 1 Buay Madang. It aims to provide accessible and engaging guidance for prospective students and parents, using a simple three-stage development process: pre-production, production, and post-production.The results reveal that 3D animations effectively enhance understanding and communication of the registration process. Feedback shows 85% of respondents found the guidance helpful, and 90% appreciated its engaging format. This study underscores the value of 3D animation in clarifying information and improving school administration efficiency.   Keywords: 3D Animation, New Student Registration Procedure, SMKN 1 Buay Madang